Novel antigens for RSV vaccines. (August 2015) - Graham, Barney S; Modjarrad, Kayvon; McLellan, Jason S
Highlights: There are multiple neutralizing antibody binding sites on F protein and at least one on G protein. The most potent neutralizing antibodies recognize sites exclusively on the prefusion conformation of F. mAbs with intermediate neutralizing potency recognize two sites present on both pre-F and post-F. F immunogens stabilized in a pre-F conformation improve prospects for an effective RSV vaccine. Abstract : Respiratory syncytial virus (RSV) remains a leading global cause of infant mortality and adult morbidity. Infection, which recurs throughout life, elicits only short-lived immunity. The development of a safe and efficacious vaccine has, thus far, been elusive. Recent technological advances, however, have yielded promising RSV vaccine candidates that are based on solving atomic-level structures of surface glycoproteins interacting with neutralizing antibodies. The class I fusion glycoprotein, F, serves as the primary antigenic component of most vaccines, and is the target of the only licensed monoclonal antibody product used to reduce the frequency of severe disease in high-risk neonates. However, success of prior F-based vaccines has been limited by the lack of understanding how the conformational rearrangement between a metastable prefusion F (pre-F) and a stable postfusion F (post-F) affected the epitope content. Neutralizing epitopes reside on both conformations, but those specific to pre-F are far more potent than those previously identified and present on post-F. The solution of the pre-F structure and its subsequent characterization and stabilization illustrates the value of a structure-based approach to vaccine development, and provides hope that a safe and effective RSV vaccine is possible.